Benchmarking medium voltage feeders using data envelopment analysis: a case study - K. T. M. U Hemapala; H. M. J. N Herath; O. V. Gnana Swathika (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Feeder performance evaluation is a key component in improving the power system network. Currently there is no proper method to find the performance of Medium Voltage Feeders (MVF) except the number of feeder failures. Performance benchmarking may be used to identify actual performance of feeders. The results of such benchmarking studies allow the organization to compare feeders with themselves and identify poorly performing feeders. This paper focuses on prominent benchmarking techniques used in international regulatory regime and analyses the applicability to MVFs. Data Envelopment Analysis (DEA) method is selected to analyze the MVFs. Correlation analysis and DEA analysis are carried out on different models and then the base model is selected for the analysis. The relative performance of the 32 MVFs of Western Province, Sri Lanka is evaluated using the DEA. Relative efficiency scores are identified for each feeder. Also the feeders are classified according to the sensitivity analysis. The results indicate that the DEA analysis may be conveniently employed to evaluate the performance of the MVFs. The evaluation is carried out once or twice a year with the MV distribution development plan in order to identify the performance of the feeders and to utilize the available limited resources efficiently.